Pressure Drop Analysis of Turbine Housing Model with Circular Sliced Pipe for Micro Hydropower Generation - Abduh, Moh; Orfa, Lourina Evanale; Sulianto, Sulianto; Iqbal, Khairul (Graduate School of Universitas Syiah Kuala, 2024)
Energy independence is a government program aiming to meet society's energy needs evenly. Steps to increase energy independence in the new and renewable energy sector include hydro-energy generation. One of the important components of a hydro generator is the penstock pipe and turbine housing, which channels water and then pushes and drives (spins) the turbine with the flow of water to produce electrical energy. The turbine housing flow design innovation must provide a function as an optimal fluid conductor by minimizing the resistance that occurs when fluid flows towards the turbine housing and rotates the turbine optimally. The scope of this research includes analysis of the phenomenon of energy loss flowing in circular pipe slices in hydroelectric power plant turbine housings with influencing factors such as friction, turbulence, and flow resistance, as well as measuring the pressure drop in circular pipe slices. The model developed is a circular slice bend with angles of 180 degrees, 270 degrees, 360 degrees, and 450 degrees, taking into account the optimal curvature ratio (R/D) of 3.5. Based on previous research, 90-degree wedge bends with many slices (n_(90-degree)) 4 to 6 or 4 and pressure drop coefficient (C_(pd-th)) obtained 180-degree (0.333 0.200), 270-degree (0.445 0.277), 360-degree (0.527 0.339), 450-degree (0.587 0.390) with a bend length L, an elevation reduction angle and a 1.5D upstream-downstream elevation difference to avoid contact between the upstream and downstream bends. The results obtained from this research are the slice modules that can be used and the resistance coefficient values that arise from the slice modules. The more slices selected according to the angle of inclination chosen, the smoother the resulting circular bend shape and the lower the resistance value, but the work will be more difficult. The most optimal slice module is the number of slices that allow its implementation, and the resistance coefficient is small. By knowing the optimal resistance coefficient value, the resulting pressure drop can be predicted to maximize the thrust to rotate the turbine.